2021
DOI: 10.12998/wjcc.v9.i6.1359
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive tools based on immune biomarkers for the diagnosis of central nervous system graft-vs-host disease: Two case reports and a review of the literature

Abstract: BACKGROUND Central nervous system graft- vs -host disease (CNS-GVHD) is a rare cause of CNS disorders after allogeneic hematopoietic stem cell transplantation. Currently, establishing a diagnosis of CNS-GVHD is challenging because the diagnostic criteria and diagnostic methods are not well defined and many confounding factors need to be ruled out. CASE SUMMARY Here, we present two patients with CNS-GVHD. Both patients with a history of acute G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Histology most frequently showed a lymphocytic vasculitis followed by microglial involvement [ 34 36 ]. Antibodies and immune biomarkers have been detected in a subset of patients [ 37 39 ]. Most responded to immunosuppressive treatment.…”
Section: Immune- or Cellular-mediated Neurotoxicity After Hct And Ctmentioning
confidence: 99%
“…Histology most frequently showed a lymphocytic vasculitis followed by microglial involvement [ 34 36 ]. Antibodies and immune biomarkers have been detected in a subset of patients [ 37 39 ]. Most responded to immunosuppressive treatment.…”
Section: Immune- or Cellular-mediated Neurotoxicity After Hct And Ctmentioning
confidence: 99%
“…Due to the rarity of CNS-GVHD and the difficulty to distinguish the disease from other mediators of CNS toxicity, biomarkers to identify CNS-GVHD would be highly desirable. IgG index in the CSF is an indicator of neurological disorders like multiple sclerosis, intrathecal inflammation ( 35 , 36 ). Another study indicated that Blood Brain Barrier (BBB) impermeability, IgG –Synthesis index are early indicators of CNS demyelination ( 37 ).…”
Section: Human Studies On Cns-gvhdmentioning
confidence: 99%
“…Another study indicated that Blood Brain Barrier (BBB) impermeability, IgG –Synthesis index are early indicators of CNS demyelination ( 37 ). In addition to this, increased BBB permeability, elevated myelin basic protein in blood and CSF are some of the immune markers that could be tested for their validity as biomarkers for CNS-GVHD ( 36 ). Identifying the immune biomarkers that predict damage to neurons, glial cells and myelin membranes may help diagnose CNS-GVHD.…”
Section: Human Studies On Cns-gvhdmentioning
confidence: 99%